Occurrence, distribution, and driving environmental factors of quaking aspen regeneration by seed in the Cameron Peak Fire burn scar - Carter, Sarah, author; Hart, Sarah, advisor; Rhoades, Charles, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2024)
As a result of the increasing frequency and severity of wildfires in the mountain west region of North America, greater mortality of montane and subalpine forests has led to changes in forest regeneration patterns and species composition. Increased drought conditions pre- and post-fire due to warming climate and destruction of existing seed have led to loss of historically conifer-dominant forests. This has subsequently opened a niche for post-fire aspen establishment, particularly through seed. The understanding of aspen regeneration by seed is understudied in comparison to the more broadly emphasized vegetative reproduction: a process which is limited spatially by the presence of surviving root networks and a lack of adaptive capacity of clone genetics. In this study, we aimed to (1) quantify the presence and density of post-fire aspen seedling establishment and (2) assess the environmental drivers of post-fire seedling establishment in a recent burn scar in northern Colorado. Two growing seasons following the fire, we conducted field surveys at 38 sites within the Cameron Peak Fire burn scar. We aimed to quantify regeneration of all tree species, including aspen as well as the dominant pre-fire conifers ponderosa pine (Pinus ponderosa), lodgepole pine (Pinus contorta), subalpine fir (Abies lasiocarpa), and Engelmann spruce (Picea engelmannii). Across our study area we found widespread establishment of aspen seedlings, particularly at high elevations, where soil moisture is less limiting. Given the occurrence of aspen seedlings within a site, we found seedlings were most likely to occur in moss seedbeds, near large coarse woody debris, and within microsite concavities, where soil moisture availability is likely higher. Collectively, our findings highlight the importance of moisture availability for the germination and initial survival of aspen seedlings. Further we found occurrence of aspen seedlings far outweighed that of any conifer species. These findings support projected changes in forest composition, species dominance, and range shift following stand replacing fire to favor early successional species such as aspen. The successful dispersal and establishment of aspen seeds in large, high severity burned patches have potential to facilitate the range shift of aspen forests towards higher elevations. These implications become more prevalent as changes in climate increase the risk of high severity fires and loss of seed sources, while decreasing suitability for montane and subalpine forest species to persist and regenerate.
Keywords: forestry; wildfire; regeneration; aspen